The Development of Hallwachs Miracle Novel as a Media Science Literacy in Learning Photoelectric Topic - Purwahida, Rahmah; Yanez, Maria Angelica; Nabilah, Norma (Program Studi Pendidikan Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2023)
This study aims to develop a novel entitled